Makna dan Nilai Tuturan Popas Lata Pasca Nikahan pada Etnik Lamaholot di Desa Puor Pulau Lembata - Maria Lambertina Beto Lamak; Simon Sabon Ola; Anastasia J. M Leda (Lembaga Yasin AlSys, 2026)
The preservation of the Lamaholot community’s oral traditions is important because the post-marital Popas Lata ritual utterances contain social meanings and cultural values that contribute to maintaining the identity of the community of Puor Village, Lembata Island. This study aimed to describe the social meanings, embedded values, and role of Popas Lata utterances in preserving the traditions and culture of the Lamaholot ethnic group. The study employed a qualitative descriptive method with a linguistic anthropology approach. The research data consisted of utterances in the Popas Lata ritual, which were analyzed based on their meanings, values, and functions in community life. The results showed that the Popas Lata ritual represents the transition in the bride and groom’s social status, the unification of two extended families, spiritual purification, and the strengthening of interclan solidarity. These utterances contain moral, social, and religious values that serve as guidelines for married life and social relationships within the community. In addition, Popas Lata utterances function as a medium for transmitting oral literature, preserving the Lamaholot language, strengthening customary law, maintaining ancestral cosmology and beliefs, and affirming the dignity of women in Lamaholot culture. This study concluded that the Popas Lata ritual is not merely a series of post-marital customary practices but also serves as a means of transmitting cultural values and strengthening the identity of the Lamaholot community. These findings emphasize the importance of documenting, preserving, and transmitting ritual utterances to younger generations to maintain the sustainability of local culture amid modernization.